Impact of Servant Leadership on Project Success Through Mediating Role of Team Motivation and Effectiveness: A Case of Software Industry. (September 2022) - Ellahi, Abida; Rehman, Mobashar; Javed, Yasir; Sultan, Fahd; Rehman, Hafiz Mudassir
Project management in today's intensely competitive environment has compelled organizations to adopt project management approach for better business results. Therefore, current research study aims to investigate the impact of servant leadership on project success with the mediating role of team motivation and team effectiveness in the software industry. A field survey was conducted, using a questionnaire as a survey tool. Data were collected from 219 respondents who have been working as team members of software development projects. The statistical results were obtained using the SPSS Process macro. The results show project managers need to exhibit a servant leadership style due to its strong influence on project success, albeit through team motivation and effectiveness. The findings from this study contribute to the field of leadership and project management along with the field of information systems and software engineering.